Simulation-based Analysis System of Glucose-Insulin Dynamics in Type 1 Diabetes Mellitus - Mohd Daud, Nur Atikah; Mohd Sabri, Aina Farhiyah; Mahmud, Farhanahani (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2017)
This project presents the development of an analysis system via simulation approach of glucose-insulin dynamics in a virtual Type 1 Diabetes Mellitus (T1DM) patient: Hovorka diabetic model using MATLAB Graphical User Interface (GUI). This analysis system is developed for a convenient technique in studying the interaction of insulin on blood glucose level based on meal and insulin taken. Several simulations of glucose-insulin dynamics have been conducted using the developed system to study the effect of patient body weight, a number of meal intake and amount and timing of insulin injection to the changes of blood glucose concentration.